Evaluation of Sa210 Grade A1 Steel Degradation Through Hardness and Microstructural Changes After High Temperature Exposure - Yayang Rusdiana; Rio Pudjidarma Santoso; Winarto Winarto (Green Publisher Indonesia, 2026)
SA210 Grade A1 steel pipes are ferritic-pearlitic steels which are commonly used in subcritical boilers. This study investigates degradation characteristics material of SA210 Grade A1 boiler steel under high-temperature operating conditions. The research examines the relationship between microstructural grain size and material hardness under control spheroidization heat treatment (SHT) with time and temperature as parameters. The virgin specimens of SA210 Grade A1 were subjected to temperatures of 600 °C, 660 °C, and 720 °C for durations ranging from 1 h to 100 h, followed by microstructural observation using optical microscopy and Vickers microhardness testing in accordance with ASTM E112 and ASTM E384-17 standards. The findings reveal that higher temperatures and longer exposure times promote pearlite spheroidization and grain size growth, which result in progressive hardness value of the material SA210 Grade A1. The hardness decreased from 167.87 HV in the virgin condition to 121.80 HV at the highest SHT parameter (720 °C – 30 h), corresponding to a 27.4 % reduction. Statistical regression modelling analysis indicated a strong correlation between hardness degradation and material hardness values against thermal exposure at high temperatures. These findings confirm that temperature is the dominant factor initiating grain size coarsening, while exposure duration governs the extent of microstructural degradation. The established correlation provides a simple yet quantitative approach for remaining life assessment of ferritic-pearlitic boiler steels operating under high-temperature service conditions.